Ampyre Sdn. Bhd. / Muhammad Nur Hadi Mohd Azmi ... [et al.] - Mohd Azmi, Muhammad Nur Hadi; Md Ramli, Muhammad Nur Fawwaz Haiqal; Yusof, Siti Nurhanani; Rahmat, Wafiya Wajha; Abdul Razak, Dhabitah (2025)
Ampyre Sdn. Bhd. is a vibrant manufacturer located at Unit C4, Kawasan Perindustrian, Jalan 70300 Seremban 2, Negeri Sembilan. Our mission to create sustainable innovations drives us to design and manufacture environmentally friendly products for today's consumers. Our flagship product, Aquaflex, is a foldable and portable intelligent bottle, designed for the eco-friendly, youthful, and mobile generation. Combining simplicity, eco-friendliness, and the latest technology, this new product is going to revolutionize the reuse bottle market. Our goal is to become the leader in the smart bottle industry, creating products that not only decrease the amount of single-use plastic waste but that also are a convenient and fashionable way to meet everyday hydration demands. This Aquaflex can go with you anywhere, to outdoors, work, studying, traveling, anything. We built it cool, good-looking, strong, and attractive, and you know, that is our answer.